Alternative perspectives on psychiatric validation : DSM, IDC, RDoC, and Beyond - Zachar, Peter; Stoyanov, Drozdstoj; Aragona, Massimiliano; Zhablenski, Asen V. (Asen Veniaminov) (International perspectives in philosophy and psychiatry., 2015)
Many of the current debates about validity in psychiatry and psychology are predicated on the unexpected failure to validate commonly used diagnostic categories. The recognition of this failure has resulted in, what Thomas Kuhn calls, a period of extraordinary science in which validation problems are given increased weight, alternatives are proposed, methodologies are debated, and philosophical and historical analyses are seen as more relevant than usual.